Peningkatan Pemahaman Soft Power Diplomacy dan Proyeksi Kebijakan Luar Negeri Indonesia Mahasiswa Prodi Ilmu Hubungan Internasional Universitas Tanjungpura - Hardi Alunaza; Arif Wicaksa; Thomas Ardian Siregar (I-Com: Indonesian Community Journal, 2025)
This community service activity is based on the fact that students need to understand about the role of soft power diplomacy and the projection of Indonesia's foreign policy in changing world politics. This community service activity was carried out at Tanjungpura University in February 2025 online through a zoom metting conference. This community service activity was carried out with a form of activity implementation consisting of material delivery, question and answer session, as well as documentation and final reporting of activities. The first sub-topic addresses the role of soft power diplomacy emphasizes the use of soft power, Indonesia's public diplomacy strategy through national branding 2+1, and public diplomacy assets. While the second sub-matter education is about Indonesia's foreign policy projections which are divided into several points, namely an explanation of Indonesia's move away from the West, response to US protectionism, response to EU trade policy, Indonesia's position on the Israel-Palestine issue, Russia - Ukraine, ASEAN in Indonesia's foreign policy, and issues related to Indonesia and BRICS.